2020
DOI: 10.3390/rel11030129
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of the Centrality and Content of Religiosity for Explaining Islamophobia in Switzerland

Abstract: Research on Islamophobia in Switzerland, and on the role of religiosity in relation to Islamophobia, is in its infancy. Against this background, we analyzed data from an online survey conducted in Switzerland on “Xenosophia and Xenophobia in and between Abrahamic religions”. The results of a multivariate analysis revealed that, besides right-wing authoritarianism, social dominance orientation, and political orientation, indicators related to religion play a crucial role. We found that the greater the role of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
9
0
2
Order By: Relevance
“…Importantly, similar effects have not been consistently observed for more general measures of religiousness, including the Centrality of Religiosity Scale, which describes the subjective importance of religious meanings within one's personality structure ( Huber & Huber, 2012 ). For example, Yendell and Huber (2020) found that non-Muslim Swiss adults who scored higher on religion's centrality, unlike religious fundamentalists, had more positive attitudes toward Islam. Furthermore, a recent investigation showed that while high levels of religiosity are inconsistent with high valuation of science in some cultures, religiosity and science might be entirely compatible in other countries, such as Iran ( Payir et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, similar effects have not been consistently observed for more general measures of religiousness, including the Centrality of Religiosity Scale, which describes the subjective importance of religious meanings within one's personality structure ( Huber & Huber, 2012 ). For example, Yendell and Huber (2020) found that non-Muslim Swiss adults who scored higher on religion's centrality, unlike religious fundamentalists, had more positive attitudes toward Islam. Furthermore, a recent investigation showed that while high levels of religiosity are inconsistent with high valuation of science in some cultures, religiosity and science might be entirely compatible in other countries, such as Iran ( Payir et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One important finding is that, of the many factors, religiosity contributes more to explaining variance than, say, social trust, political position and national identity. We therefore suggest that future studies examining the relationship between religiosity and prejudice use a multi-dimensional model such as the CRS (see also Yendell Huber 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Lundby et al (2017) analyzed relationships between religiosity and political attitudes in Scandinavia and found that most Scandinavians associate 'religion' with conflict and half of the population perceives Islam as a threat to their national culture. Research demonstrates that there are manifestations of Islamophobia in France and the UK (Najib and Hopkins, 2020), Belgium (Mescoli, 2019), Sweden (Bevelander and Otterbeck, 2012), and Switzerland (Yendell and Huber, 2020). Hence, based on the epistemology of journalism culture, we ask: RQ3: How is religion in any way related to the news coverage of the European refugee issue in Europe and China?…”
Section: Influences Beyond News Organizationsmentioning
confidence: 99%